2015
DOI: 10.1007/s10096-015-2351-8
|View full text |Cite
|
Sign up to set email alerts
|

Ureaplasma parvum and Ureaplasma urealyticum detected with the same frequency among women with and without symptoms of urogenital tract infection

Abstract: There is mounting evidence stating that Ureaplasma urealyticum causes non-gonococcal urethritis in males, whereas Ureaplasma parvum does not seem to be of clinical significance. However, the clinical role of U. parvum and U. urealyticum in lower urogenital tract infections in females remains unclear. The aim of the study was to determine the frequency of U. parvum and U. urealyticum among 145 Ureaplasma spp. culture-positive women with symptoms of lower urogenital tract infection (n = 75) and those without (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
33
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 24 publications
8
33
1
2
Order By: Relevance
“…There are no case–control studies or other appropriate evidence that M. hominis , U. parvum or U. urealyticum causes an inflammatory vulvovaginitis . The number of leucocytes in vaginal smears are also not increased in women positive for only ureaplasmas …”
Section: Womenmentioning
confidence: 99%
See 2 more Smart Citations
“…There are no case–control studies or other appropriate evidence that M. hominis , U. parvum or U. urealyticum causes an inflammatory vulvovaginitis . The number of leucocytes in vaginal smears are also not increased in women positive for only ureaplasmas …”
Section: Womenmentioning
confidence: 99%
“…The prevalence of M. hominis , U. urealyticum and U. parvum in non‐pregnant sexually active symptomatic and asymptomatic women, measured by molecular tests including species differentiation, has ranged between 3.1–15% #bib5.2–20% and 20–89%, respectively . The large variation in prevalence probably reflects both methodological and true population differences, in particular in the prevalence of BV, the most important confounder.…”
Section: Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…U. parvum is isolated more frequently from the lower genital tract of females than U. urealyticum (158,159,(164)(165)(166), and serovar 3 is the most common serovar isolated from females in the United States and Australia (116,158,163). Ureaplasma colonization of the female lower genital tract has been associated with numerous factors, including ethnicity (particularly African-American, Central/West African, and Indigenous Australian women) (123,167,168), age (most prevalent in the 14-to 25-year age group; carriage declines with increasing age) (165,167), the number of recent sexual partners (123,168), the use of nonbarrier contraceptives (123), level of education (167), age of first sexual intercourse (123), and intrauterine devices (167,169). Ureaplasma spp.…”
Section: Ureaplasma Spp Are Commensals Of the Female Lower Genital Tmentioning
confidence: 99%
“…Ureaplasma spp. are considered to be commensal organisms within the female lower genital tract due to (i) their high prevalence and (ii) studies demonstrating no differences in the rates of endocervical Ureaplasma colonization between women of reproductive age with and those without symptoms of genital infection (165,166). However, others have reported that Ureaplasma spp.…”
Section: Ureaplasma Spp Are Commensals Of the Female Lower Genital Tmentioning
confidence: 99%